“Age Assessment In Children By Two Methods, Measuring Tooth Root Apex: A Radiographical Forensic Study” (Journal of Pharmaceutical Negative Results, 2023)
Background And Objectives: Age estimation in children is a fundamental question in forensic medicine and in treatment planning. It is needed to estimate the age of living individuals to answer a variety of legal questions like status of majority and criminal liability such as in child marriage, commercial and sexual harassment, in situations where birth data is lacking or doubted. Various methods have been proposed for assessment of the dental maturation, but the most widely applied method of dental age estimation is being proposed by Demirijian et al. In 2006, Cameriere also developed a new method of assessing chronological age in children based on the relationship between age and measurement of open apices in tooth roots. With this background, the present study was conducted to estimate the dental age of the children from open and closed apex.Methodology: 99 digital panoramic radiograph of patients aged between 5 and 15 years were taken randomly using digital panoramic machine after taking consent of patient’s parents. Dental age estimation was performed using maturity score and equations by Demirijians and Cameriere method. The number of teeth with complete root development, i.e., apical ends of the roots completely closed (N0), were counted. Teeth with incomplete root development, i.e., with open apices, were also examined and the distance between the inner sides of the open apex was measured.Results & Conclusion: Both the methods were found to be statistically significant with p-value <0.001. Both the methods can be used for age estimation. In Demirijian’s method, the accuracy was found more comparative Cameriere’s method. The maximum accuracy was seen in 11-12 years of age in Demirijian’s method where as in Cameriere’s method the accuracy was almost same in all the age groups and the precision was seen in males than in females, on comparison, the great accuracy was found in Cameriere’s age estimation method when compared to the Demirijian’s method. Dental maturity can be used to assess chronological age in children either by Demirijian’s or Cameriere’s method, among these Demirijian’s method found to be more accurate.